2021
DOI: 10.1039/d1py01067k
|View full text |Cite
|
Sign up to set email alerts
|

Amino-acid-substituted polyacetylene-based chiral core–shell microspheres: helix structure induction and application for chiral resolution and adsorption

Abstract: The chiral composite materials were synthesized by the helical polymers directly compounded with the substrate at present, due to changes in chemical bonds and steric hindrance during the compounding process...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Amino acids as natural chiral molecules were also carried out as the monomers. At the same time, the derivative of amino acids is necessary to contain the alkynyl or vinyl units for polymerization [7981]. The group of Qi prepared chiral core–shell microspheres using l ‐alanine‐substituted polyacetylene as the shell [79].…”
Section: Design Synthesis and Application Of Helical Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids as natural chiral molecules were also carried out as the monomers. At the same time, the derivative of amino acids is necessary to contain the alkynyl or vinyl units for polymerization [7981]. The group of Qi prepared chiral core–shell microspheres using l ‐alanine‐substituted polyacetylene as the shell [79].…”
Section: Design Synthesis and Application Of Helical Polymersmentioning
confidence: 99%
“…At the same time, the derivative of amino acids is necessary to contain the alkynyl or vinyl units for polymerization [7981]. The group of Qi prepared chiral core–shell microspheres using l ‐alanine‐substituted polyacetylene as the shell [79]. Importantly, the presence of copper(II) ion contributed to a one‐handed helix validated by CD spectra.…”
Section: Design Synthesis and Application Of Helical Polymersmentioning
confidence: 99%
“…Following the discovery of CPs, Alan J. Heeger, Alan G. MacDiarmid, and Hideki Shirakawa received the Nobel Prize for Chemistry in 2000 [96]. The CPs most frequently encountered in scientific research are PPy [97][98][99][100][101], PANI [102][103][104][105], PEDOT [46,[106][107][108][109], PT [110][111][112][113], and polyacetylene [114][115][116], the chemical structures of which are shown in Figure 3. This type of polymer is usually obtained by electrochemical polymerization, a process that takes place in a solution that includes the solvent, the polymerizable monomer, and the electrolyte.…”
Section: Cps and Mips Used To Determine Phe Tyr And Tryptmentioning
confidence: 99%
“…In a pioneering work, Deng and coworkers explored the self-assembly of poly(acetylene)s (PAs) into chiral nanospheres via nanoprecipitation. [48][49][50] However, the relationship between the secondary structure of a PA and its aggregation capacity was not explored in these studies. In the literature, it is found that the nanostructuration of helical polymer-metal complexes (HPMCs) occurs using PPAs as helical polymers and different metal ions as crosslinking agents.…”
Section: Introductionmentioning
confidence: 99%